Prekäre (Kultur-)Kämpfe? Die Verhandlung gesellschaftlicher Verhältnisse im Diskurs zu Prekarisierung - Freudenschuß, Magdalena (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2010)
Precarity became an issue in public discourse in German speaking media throughout 2006. In this article the author takes a closer look on the symbolic negotiations on precariousness/precarity and its references to neo-conservative reasoning undertaken in the public media discourse. Who is designated as the precarious subject -- and to what extent do discursive designations legitimate social inequalities? Public discourse is to be understood as an ambivalent and multifaceted field of negotiations on society and social justice. As such, it is a field where interpretations of societal changes try to gain a hegemonic position and where they are at the same time challenged, disrupted and irritated. Thus, the article points out some hegemonic and counter-hegemonic moments within the public discourse on precarity.